2016
DOI: 10.12968/jowc.2016.25.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Wound dressing following primary total hip arthroplasty: a prospective randomised controlled trial

Abstract: The reduction in frequency of dressing changes coupled with low levels of wound leakage observed using the combination of the glue and nonabsorbent dressings (O+T), makes this combination of wound closing products ideal for facilitating enhanced recovery and early discharge programmes in elective hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…No significant results for the additional application of cyanoacrylate glue on the incidence of SSIs were reported from the RCT (Table and Figure ). Siddiqui et al reported an increase in SSI in the intervention group (SSI = 3) in comparison with the control group ( SSI = 1) ( P = 0.62).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…No significant results for the additional application of cyanoacrylate glue on the incidence of SSIs were reported from the RCT (Table and Figure ). Siddiqui et al reported an increase in SSI in the intervention group (SSI = 3) in comparison with the control group ( SSI = 1) ( P = 0.62).…”
Section: Resultsmentioning
confidence: 96%
“…Wound closure with subcuticular sutures and subsequent application of cyanoacrylate glue was used in the intervention arm of all included articles. Siddiqui et al further dressed the wound with Opsite in both arms (United Kingdom) . Ozturk et al compared subcuticular sutures and antibiotic ointment with or without cyanoacrylate glue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations